Making sense of data II: a practical guide to data visualization, advanced data mining methods and applications - Horníková, Adriana
Recenzia publikácie Glenna J. Myatta a Wayna P. Johnsona: Making sense of data II: a practical guide to data visualization, advanced data mining methods and applications. Problematika techniky dolovania dát zo štatistického hľadiska. Popis jednotlivých kapitol.